Roman Warfare - Goldsworthy, Adrian; General Editor : John Keegan (London Cassell & Co., 2000)
A well written and well illustrated general history of Roman warfare from the conquest of Italy to the collapse of the Empire. Adrian Goldsworthy is selective in the wars that he describes, which include the epic wars with Carthage and the Hellenistic world, the siege of Jerusalem and Caesar's campaigns in Gaul. Twenty maps provide details of the locations of forts, defences and shifts in territorial power. The methods and tactics of war, the evolution of the army and the social and political aspects associated with militarism, are discussed throughout.
Include Index, Glossary, Maps and Colored Illustrations.
Keywords: Rome (Empire) -- Military Art and Science -- Rome -- History